Fbxl11 Is a Novel Negative Element of the Mammalian Circadian Clock. (August 2015) - Reischl, Silke; Kramer, Achim
In mammals, molecular circadian rhythms are generated by autoregulatory transcriptional-translational feedback loops with PERIOD/CRYPTOCHROME containing complexes inhibiting the transcription of their own genes. Although the major circadian oscillator components seem to be identified, an increasing number of additional factors modulating core clock component functions are being discovered. In a systematic screen using short hairpin RNA in human clock reporter cells, we identified FBXL11 (also known as KDM2A), a histone-demethylase, whose gene dosage is crucial for a correct circadian period. Knockdown of FBXL11 leads to period shortening and overexpression to period lengthening. In addition, altering FBXL11 gene dosage modulates clock gene transcript levels, most prominently that of Nr1d1 . FBXL11 exercises its role in the mammalian circadian clock by acting as a negative element on CLOCK/BMAL1 and RORα-induced transcription. It binds directly to the promoter regions of CLOCK/BMAL1-regulated genes via a CXXC-type zinc finger motif in a circadian phase-dependent manner; however, the histone-demethylase activity of FBXL11 is not required for transcriptional repression. Therefore, we propose FBXL11 as a novel component of the circadian clock that regulates the circadian gene expression by a so far unknown mechanism.